CHALLENGES FOR AGRICULTURAL POLICY IN THE SERVICE-DRIVEN ECONOMIC SYSTEM - Vidickiene, Dalia; Gedminaite-Raudone, Zivile (Economics of Agriculture, 2018)
During last decades the essential shift occurred in the structure of the economy from industrial product-driven to the post-industrial service-driven economic system. A growing number of manufacturing firms throughout the world are shifting from selling goods to offering more and more services alongside their products. This movement is termed the "servitization". The movement is pervading almost all industries but still is weak in agriculture. The aim of the paper is to draw an agricultural sector-specific picture of servitization and discuss the differences between the business models of product-driven and service-driven farms. Servitization of farming is a transformational process that requires rethinking all aspects of the business: production structure and methods, marketing, pricing, service delivery infrastructure and financial management. The aims and means of current agricultural policy should be transformed in accordance with the emerging new business vision of the post-industrial farmers generation. The article analyses the needs and perspectives to develop agricultural policy in line with the success factors of the service-driven economic system and highlights the main new post-industrial rural policy trends, which corresponds to the needs of new farmers generation oriented towards servitization of farming in the new programming period after 2020.